Research on Three-dimensional Modeling of Urban Buildings based on CityGML - Li, Xuan (Scientific Journal of Technology, 2025)
In the rapidly advancing wave of urbanization, 3D city modeling technology has gradually become a key means of urban planning and management. CityGML, based on XML, is a three-dimensional information modeling specification that covers various elements such as urban architecture and terrain. This article aims to explore the methodology of using CityGML to construct 3D models of urban architecture, elaborating on the modeling steps including data collection, feature selection, model refinement, and data storage. Key technologies such as geometric construction, semantic construction, texture matching, and data interaction are analyzed. With the standardized CityGML model, urban planning departments can more efficiently carry out tasks such as urban planning, building supervision, and disaster prevention, providing reference for promoting the application of CityGML in the field of urban model construction.